Interface engineering of Co-CoMoSx heterostructure nanosheets for an efficient alkaline oxygen evolution reaction. Issue 21 (7th October 2022) - Mao, Xiaoqing; Liu, Zhihang; Feng, Huiyan; Chen, Zhenyu; Shen, Pei Kang
Abstract : Co-CoMoS x nanosheet arrays show an outstanding electrocatalytic oxygen evolution performance (Tafel slope b = 64.79 mV dec −1, η 100 = 292 mV, η 1000 = 402 mV) and remarkable stability in an alkaline solution. Abstract : It is very essential to develop inexpensive and efficient oxygen evolution catalysts for water splitting. Interface engineering can modify the local electronic structure of active sites, which is one of the important ways to enhance catalytic activity. Herein, we prepared Co-CoMoS x heterostructure nanosheet arrays by a two-step hydrothermal method. Because of the strong electronic interaction between the components of Co-CoMoS x, Co-CoMoS x nanosheet arrays show an outstanding electrocatalytic oxygen evolution performance (Tafel slope b = 64.79 mV dec −1, η 100 = 292 mV, η 1000 = 402 mV) and remarkable stability in alkaline solution. Remarkably, the Co-CoMoS x ‖PS-MoNi (phase-separated Mo–Ni alloy) electrolytic cell can facilitate water splitting at a low voltage of 1.48 V to deliver a current density of 10 mA cm −2 and exhibits durability for up to 150 hours. This study puts forward a promising direction for the synthesis of high performance heterostructure catalysts for oxygen evolution.